Reflecting on NEXUS Gains’ outcomes in Central Asia: Upstream responses to the Aral Sea disaster - CGIAR Initiative on NEXUS Gains (CGIAR System Organization, 2024)
NEXUS Gains has worked for three years at the nexus of water, energy, food, and ecosystems (WEFE) in Central Asia. While the drying of the Aral Sea is the region’s most visible and dramatic environmental disaster, it is part of a broader pattern of environmental degradation that includes the salinization of nearly half of all irrigated land, soil erosion, water scarcity, and biodiversity loss. Ninety percent of freshwater withdrawals in Central Asia are consumed by agriculture, now mostly for cereals and in particular wheat, but also cotton production. Half the population lives in areas of high water stress, and renewable water resources have declined sharply since the 1960s. All of this has been exacerbated by a 1.5°C temperature rise and the melting of glaciers. NEXUS Gains collaborated with Central Asian governments and stakeholders to counter further environmental degradation through the development and testing of integrated WEFE nexus solutions.